Alkaline-Earth Metal Complexes: Mixed Ligand Complexes of Alkaline-Earth Metal Salts of Some Organic Acids with 5,7-Dinitro-oxine - Prakash, Dharam; Kumar Yadav, Ashok (Asian Journal of Chemistry, 2010)
A number of mixed ligand complexes of alkaline-earth metal salts of some acids like 1-nitroso-2-naphthol (1N2N), o-nitrophenol (ONP), 2,4-dinitrophenol (DNP), salicylaldehyde (Sal.H) and salicylic acid (Sal.A) with 5,7-dinitro-oxine have been synthesized and characterized by elemental analysis, conductivity measurement and FTIR-spectral studies.